Biomimetic high-intensity superhydrophobic metal rubber with anti-corrosion property for industrial oil–water separation. (8th January 2019) - Ren, Zhiying; Wen, Gang; Guo, Zhiguang
Abstract : In this work, a superhydrophobic metal rubber with excellent water repellency, mechanical durability, corrosion resistance and oil/water separation properties was prepared by a facile and scale-up chemical etching method and a straightforward modification. Abstract : Metal rubber (MR) using steel wires is increasingly desired, particularly for the practical process of industrial production. However, realizing multifunctionality of MR during its service remains challenging. In this work, for the first time, we present a simple chemical etching method and a straightforward modification to render an MR surface made of stainless steel wires superhydrophobic while strengthening its corrosion resistance. Creation of a lotus-like hierarchical structure was performed by a two-step chemical etching process. The superhydrophobic MR with a water contact angle of about 152° and a sliding angle of about 5° can be used for effective and rapid oil/water separation. And the water repellency property of the superhydrophobic MR still remains even after 10 abrasion cycles with sandpaper (400 cW), indicating excellent mechanical durability. Additionally, the corrosion resistance of the superhydrophobic MR is much higher than that of raw MR, which will broaden its practical applications. This study expands the potential applications of functional MR, which might be a breakthrough for traditional MR-making industries.